1979
DOI: 10.2337/diab.28.8.769
|View full text |Cite
|
Sign up to set email alerts
|

Method for Large-Scale Isolation of Pancreatic Islets by Tissue Culture of Fetal Rat Pancreas

Abstract: Detailed studies of the maturation of stimulus-secretion coupling of the pancreatic B-cell requires a supply of isolated fetal islets, which has so far been difficult to obtain. To overcome this problem we have maintained minced and mildly collagenase-digested fetal rat pancreatic glands (21.5 days gestational age) in tissue culture to enable degeneration of the acinar part, leaving the endocrine cells in an isolated and surviving state. Indeed, after 1 wk in culture there was a complete separation between aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 0 publications
5
93
0
Order By: Relevance
“…The findings presented here confirm that TPA provokes secretion of insulin from the p-cells, and also suggest that the phorboi ester treatment leads to stimulation of p-cell replication. Because islets prepared according to the presently employed technique contain >90% t-cells it seems reasonable to assume that the results are representative of this particular cell type [10]. In addition, incorporation of [aH]thymidine over a 5-h labeling period has been shown to represent p-cell mitotic activity [25].…”
Section: Resultsmentioning
confidence: 99%
“…The findings presented here confirm that TPA provokes secretion of insulin from the p-cells, and also suggest that the phorboi ester treatment leads to stimulation of p-cell replication. Because islets prepared according to the presently employed technique contain >90% t-cells it seems reasonable to assume that the results are representative of this particular cell type [10]. In addition, incorporation of [aH]thymidine over a 5-h labeling period has been shown to represent p-cell mitotic activity [25].…”
Section: Resultsmentioning
confidence: 99%
“…In each experiment, all test groups received the same amount of solvent used to dissolve various drugs. We chose to use fetal islets to obtain islet tissue enriched in ␤-cells; previous studies have shown that fetal islets contain 90-95% ␤-cells, which display a full secretory response to glucose after a 5-day culture period similar to that of the adult ␤-cell (20,39).…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant Wistar rats, purchased from B & K Universal (Sollentuna, Sweden), were killed by cervical dislocation on day 21 of gestation and the fetuses rapidly removed. Islets were prepared from pancreatic glands as previously described (20,39). Briefly, the pancreata were finely chopped and digested for a short time with collagenase.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now it has been widely acknowledged that culture of fetal and neonatal B cells in media with high glucose is beneficial to their function in vitro. For example, HellerstrOm et al (1979) showed that fetal islets cultured for 8 days in medium containing 11.1-22.2 mM D-glucose responded to an acute glucose stmulation, while there was no response by islets cultured in 5.5 mM D-glucose. Furthermore, in cultured islets the low glucose decreased the cAMP response to D-glucose, which is assumed to be involved in glucose-induced insulin release or B-cell replication (Grill and Cerasi, 1974 ;Ravinovitch et al, 1978 ;Rabinovitch et al, 1980).…”
Section: Glutamine Oxidationmentioning
confidence: 99%